2017
DOI: 10.5805/sfti.2017.19.2.180
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Types of Product Review on Mobile Beauty App, Perceived Information Authenticity, Brand Attitude, Purchase Intention and e-WOM Intention

Abstract: The increase use of smartphones has paved the way for quick dissemination of online information. This has a huge influence on consumers' purchase decision making and the formation of a company's image. As such, this study focuses on product review from mobile beauty applications(apps); in particular, the perceived information authenticity. The purpose is as follows. First, to examine if there is any difference in perceived information authenticity based on the types of product review. Second, to analyze how pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…This study empirically confirmed that brand attitude, brand attachment and purchase intention are correlated variables. This aligns with previous findings that also found correlations between these variables, for example, brand attitude has a positive effect on brand attachment (Chen et al, 2017) and purchase intention (Tsang et al, 2004;Chen et al, 2008;Daugherty et al, 2008;Hartmann and Apaolaza-Ibanez, 2012;Khan and Farhat, 2012;Chun et al, 2017;Lee et al, 2017), and that brand attachment has a positive effect on purchase intention (Wu et al, 2015;Oh et al, 2016;Danyang et al, 2020;Gilal et al, 2021). The results of this study, in combination with previous findings, confirm that positive brand attitude is an important factor that helps to generate brand attachment and purchase intention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study empirically confirmed that brand attitude, brand attachment and purchase intention are correlated variables. This aligns with previous findings that also found correlations between these variables, for example, brand attitude has a positive effect on brand attachment (Chen et al, 2017) and purchase intention (Tsang et al, 2004;Chen et al, 2008;Daugherty et al, 2008;Hartmann and Apaolaza-Ibanez, 2012;Khan and Farhat, 2012;Chun et al, 2017;Lee et al, 2017), and that brand attachment has a positive effect on purchase intention (Wu et al, 2015;Oh et al, 2016;Danyang et al, 2020;Gilal et al, 2021). The results of this study, in combination with previous findings, confirm that positive brand attitude is an important factor that helps to generate brand attachment and purchase intention.…”
Section: Discussionsupporting
confidence: 92%
“…Brand attitude is also known to be an important antecedent factor that directly affects purchase intention (Tsang et al, 2004;Daugherty et al, 2008). Many studies have confirmed that favorable brand attitudes result in purchase intentions (Chen et al, 2008;Hartmann and Apaolaza-Ibanez, 2012;Khan and Farhat, 2012;Chun et al, 2017;Lee et al, 2017).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%